IMPLEMENTASI METODE MAHKAMAH BAHASA UNTUK MENINGKATKAN KEDISIPLINAN BERBAHASA INDONESIA SANTRI PONDOK PESANTREN NURUL IMAN CILACAP - Ma’ruf Rizqi Fauzani; Agnes Apryliana; Sigit Andi Prasetya Dinata (CV. Denasya Smart Publisher, 2024)
Language is a system of arbitrary sound symbols, which is used by social groups to collaborate, communicate and identify themselves. Language court is a method used in Islamic boarding schools to discipline students to speak official languages. The aim of this research is to describe the background to the use of language court methods at the Nurul Iman Islamic Boarding School in Cilacap. Then, to describe the supporting and inhibiting factors for implementing the Nurul Iman Islamic Boarding School language court method. And to describe the procedures for implementing the language court method in the Nurul Iman Islamic Boarding School environment in Cilacap. This research is qualitative descriptive research, namely research procedures in order to present descriptive data in the form of a person's written or spoken words and behavior that can be studied. The research results illustrate that students come from different regions, so there is a need for language uniformity. Then, the supporting factors are the enthusiastic students and support from administrators and teachers in overseeing it. The inhibiting factors are that the students are not very confident in using Indonesian and the students' circle of friends and the procedure for implementing the language court method is fairly systematic because first, the students become spies then look for language violators and then record them in spy paper, then the paper is handed over to the management and announced after the implementation of evening prayers and then the trial and punishment process.